PENGGUNAAN ALAT STATISTIK DALAM RANGKA PENGENDALIAN KUALITAS PRODUK MARMER PADA PT. MAKASSAR MARMER MULIA INDAH - Indra Abadi (AkMen JURNAL ILMIAH, 2015)
PT. Makassar Marmer Mulia Indah is a company engaged in manufacturing that produce marble. In order to maintain the confidence of consumers, in 2000, the company has obtained ISO 9001: 2000. The fact that it happens that the percentage of damage to marble products for each type of product on average above 6% or it can be concluded that the production process is not progressing normally. To determine the control system is functioning properly then use statistical tools and supported by the data sheet, histogram, control chart, Pareto diagram and fish bone diagram